Pembuatan Palang Penunjuk Rumah Aparat Desa sebagai Upaya Mendukung Akses Informasi di Desa Tutut, Kecamatan Sungai Mas - Mahmud Basuki; Wahyuni Febrinanisa; Nova Eliza; Mulia Risna; Randa Wilanta; Agus Badrol Auliya; Rosi Dewi Ayu; M. Kasasul Aula; Aprilla Riska Sari (Pusat Riset dan Inovasi Nasional, 2025)
This community service program aims to improve public access to information regarding the location and whereabouts of village officials' homes through the creation and installation of signposts. One of the problems faced by the people of Tutut Village, Sungai Mas District, is the lack of adequate visual information regarding the location of village officials' homes. This often makes it difficult for residents to find authorized officials when they want to express their aspirations, request information, or handle village administration. This program is an initiative of Teuku Umar University Community Service Program (KKN) students in collaboration with the village government and local community leaders. The implementation method includes identifying needs through observation and discussions with the community, coordinating with village officials to obtain data and installation permits, designing the signposts, manually painting them, and directly installing them at strategic locations within the village. The signposts are installed at points that are easily visible and accessible to the community, such as road intersections and near public facilities. The signposts are designed with striking colors and clear lettering to be easily read by residents, including those coming from outside the village. Initial results of the program indicate a very positive response from the community. Residents felt relieved because they no longer had to go door-to-door to find village officials. Furthermore, this activity was seen as a demonstration of the students' genuine concern for the real needs of the community on the ground. The presence of these signposts is considered a simple innovation yet offers significant practical and sustainable benefits. It is hoped that similar activities can be implemented in other villages, with adjustments based on the local needs of each region.